(untitled) (Physical Education, Health and Social Sciences, 2025)
Interprofessional Collaboration (IPC) is pivotal in healthcare, particularly in neonatal intensive care units (ICU). Effective Interprofessional Collaboration between nurses, physicians, and respiratory therapists in patient care can reduce hospital stays, improve the quality of care, and enhance patient health outcomes. It has been determined that Interprofessional Collaboration (IPC) is among the most significant policy strategies for overcoming healthcare staff and patient safety challenges and improving the healthcare organization. This study explores the perceptions of NICU nurses, physicians, and respiratory therapists about IPC in a tertiary care hospital in Karachi, Pakistan. It also investigates the facilitators and barriers to IPC, which impact the quality of patient care. An exploratory qualitative study was conducted through semi-structured interviews of 12 nurses, physicians, and respiratory therapists in a tertiary care hospital neonatal ICU. The study employed a purposive sampling technique, where participants were selected based on their direct engagement in patient care. Interviews were conducted in both Urdu and English, each in-depth interview takes 30-40 minutes. Data analysis proceeded with systematic text condensation, with thematic analysis to determine key patterns and themes. There were three dominant themes identified in the analysis: 1) Attitudes of health professionals toward IPC, emphasizing the significance of patient outcomes and enhanced collaboration opportunities 2) Facilitating factors of effective IPC, stressing the role of effective communication, respect, and trust and professional experience and knowledge; 3) Hindering factors to effective IPC, and the difficulty such as shortage of organizational support, power disparity, workload extension, and factors based on systems. Participants acknowledged the substantial advantages of IPC to improve patient outcomes and stressed the significance of cooperative, respectful, and well-informed practices by healthcare professionals. It also suggests the need to highlight its incorporation in education and research practices. This study adds important insight into the dynamics of IPC in a developing country’s healthcare system. It underlines the key position that IPC takes in enhancing patient outcomes and the need for systemic changes to ensure an Interprofessional healthcare culture.